Analysis and simulation of semi-active suspension control policies for two-axle off-road vehicle using full model - BenLahcene, Zohir; Faris, Waleed Fekry; Ihsan, Sany Izan (Inderscience Enterprises Ltd., 2011)
Ride comfort and vehicle handling of heavy off-road vehicles can be improved with the help of a controlled suspension system. This paper describes the impact of a semi-active and passive system on the driving behaviour of a heavy off-road 4 × 4 wheeled vehicle. The analysis is based on a military vehicle model used for simulating off-road vehicle drives and handling. The analysis covers both transient responses and transmissibility response in frequency domain. To start with, the fundamental skyhook, groundhook and hybrid principles are used for controlling. Frequency response and sprung mass accelerations, suspension and tyre deflection response in time domain are clearly improved using semi-active control policies compare to passive system.